Wireless RFID/sensor network using SAW (WiRSeNS): A feasibility study - Jeoti, V. (Institute of Electrical and Electronics Engineers Inc., 2015)
The Surface Acoustic Wave (SAW) RFID/sensor technology is increasingly becoming popular because it is passive and wirelessly addressable while being tolerant to high temperatures and pressure load. In order that the SAW sensors can be interrogated faithfully while being in the presence of considerable multipath and multiple-access interference, two key questions need to be answered - one, what suitable signal design will facilitate robust detection of sensor ID and sensing variable and two, what suitable suite of network protocols will give rise to robust and reliable data propagation through the network of interrogators. This paper presents a feasibility study of the same. Such a network for operation in industrial applications is targeted. There are certain locations inside a plant which cannot be easily accessed. These remarkably long-life and passive sensors can be installed within those locations for real time monitoring. The paper includes the background of SAW RFID/sensors, its sensing mechanisms and parameter determination is presented in this paper. Network design issues and their possible solutions are also discussed. Â© 2015 IEEE.